Parent's Stigma Towards Childhood Tuberculosis: A Multicenter Survey from Eastern Bandung Regency - Azalia Melati; Titin Rohmatin; Grashiva Putri Karina; Tika Asri; Desi Apriani; Windy Rakhmawati (STIKep PPNI Jawa Barat, 2023)
Aims: Tuberculosis-related stigma negatively influences tuberculosis prevention programs such as delayed diagnoses, poor treatment adherence, and decreased quality of life of patients. This descriptive quantitative study aimed to describe the stigma towards tuberculosis among parents. Method: A total of 30 samples taken through accidental sampling were parents who had children (0-14 years) with tuberculosis who had been treated at the public health centers. A questionnaire adapted from Van Rie TB Stigma Scale (VTSS) was used and analyzed using descriptive analysis. Result: Most parents (76.6%) had lower levels of stigma, while the others scored higher levels. Lower stigma levels can be caused by a mature mindset, good knowledge of TB information, and indicates higher hopes from parents to increase their care level for children’s development, health-seeking behavior, and support for children’s TB treatment until it is completed. Accordingly, higher stigma levels from parents might be a result of several external factors that can increase the lack of motivation for health-seeking behavior in their children’s TB treatment. Conclusion: The role of health workers is very important in reducing stigma. Health education about prevention and treatment of childhood tuberculosis is still needed because it is a source of fear and high stigma against childhood tuberculosis in society.